Utility of NS1 Antigen for Diagnosis of Dengue Virus Infection - Pramod S. Manthalkar; B.V. Peerapur (Journal of Krishna Institute of Medical Sciences University, 2017)
Background: Dengue has become a major global public health problem in the developing countries. Aim and Objectives: This study was carried out to evaluate the utility of NS1 antigen assay in early diagnosis of dengue infection. Material and Methods: The performance, detection rate of NS1 antigen assay in comparison to IgM Antibody Capture Enzyme Linked Immunosorbent Assay (MAC-ELISA) was evaluated in a single sample constituted Group 1. One thousand acute/ early convalescent sera were screened by both the assays. NS1 antigen assay was used to evaluate the efficacy of single assay in 30 acute phase sera of paediatric outpatient department, patients constituted Group II. Specificity of NS1 assay in comparison to MAC- ELISA was evaluated on 40 samples used as controls constituted group III. Results: Out of 1000 samples in Group I, 247 (24.7%) and 184 (18.4%) samples were positive by NS1 assay and MAC –ELISA respectively. Increase in the detection rate to 431 (43.1%) was seen when both the assays were used together on a single sample. NS 1 Ag positivity varied from 97.57% to 2.42% in acute and early convalescent sera, conversely IgM detection rate was 94.56% and 5.43% in early convalescent and acute phase sera respectively (P<0.0001). Twenty (66.66%) samples were positive by NS 1 assay in Group II. All 40 samples in Group III were negative showing 100% specificity of both the assays. Conclusion: NS-1 Ag assay is a useful tool for early diagnosis of dengue virus infection. When used in combination with MAC-ELISA on a single sample it significantly improves the diagnosis algorithm without the requirement of paired sera.